Staging of Schizophrenia with the use of PANSS: An international multi-center study. - Fountoulakis, Konstantinos N; Dragioti, Elena; Theofilidis, Antonis T; Wikilund, Tobias; Atmatzidis, Xenofon; Nimatoudis, Ioannis; Thys, Erik; Wampers, Martien; Hranov, Luchezar; Hristova, Trayana; Aptalidis, Daniil; Milev, Roumen; et al. (Int J Neuropsychopharmacol, 2019)
INTRODUCTION: A specific clinically relevant staging model for schizophrenia has not yet been developed. The aim of the current study was to evaluate the factor structure of the PANSS and to develop such a staging method. MATERIALS AND METHODS: Twenty-nine centers from 25 countries contributed 2358 patients aged 37.21±11.87 years with schizophrenia. Analysis of Covariance, Exploratory Factor Analysis (EFA), Discriminant Function Analysis (DFA) and inspection of resultant plots were performed. RESULTS: EFA returned five factors explaining 59% of the variance (Positive-Po, Negative-Ne, Excitement/Hostility-EH, Depression/Anxiety-DA and Neurocognition-Ncog). The staging model included four main stages with substages that were predominantly characterized by a single domain of symptoms (stage 1: Po; stage 2a and 2b: EH; stage 3a and 3b: DA; stage 4a and 4b: Ncog). There were no differences between sexes. The DFA developed an algorithm which correctly classified >85% of patients. DISCUSSION: This study elaborates a five-factor solution and a clinical staging method for patients with schizophrenia. It is the largest study to address these issues among patients who are more likely to remain affiliated with mental health services for prolonged periods of time.